Typification and an emended description of Astragalus moussavii (Fabaceae, Papilionoideae) - Ghahremaninejad, Farrokh; Nejad Falatoury, Atiye; Memariani, Farshid (Phytotaxa, 2020)
Type materials of Astragalus moussavii (Fabaceae) are designated as a lectotype and four isolectotypes. An epitype for the species is designated here too. An emended description of A. moussavii is provided with illustrations and information on several morphological characters not indicated in the protologue, including the size and shape of the terminal leaflet, petals characteristics, fruit and seed features. Based on field observations, a brief description of the habitat and data on ecology and biogeography of the species are provided and its conservation status is evaluated.